The Effect of Organization Mission Fulfillment on Emotional Exhaustion and Job Outcomes - Kaviti, Rashin (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
The purpose of this thesis is to develop and test a conceptual model that examines the effect of organization mission fulfillment on emotional exhaustion, turnover intentions, lateness attitude, job performance, and extra-role customer service. Data collected from employees in the international five-star chain hotels in Dubai, the tourism center in the United Arab Emirates. These frontline employees had frequent face-to-face or voice-to-voice interactions with customers. This study used a time lag of two weeks. Data relating to performance variables were obtained from the immediate supervisors of these employees. The results revealed that emotional exhaustion mediated the effect of organization mission fulfillment on turnover intentions, lateness attitude, job performance, and extra-role customer service. That is, employees’ perceptins of organization mission fulfillment reduced their emotional exhaustion. In this case, employees displayed lower turnover and lateness intentions, while they had higher performance in the workplace. Based on the aforementioned findings, management implications were given and limitations of the study and future research directions were provided. Keywords: Emotional Exhaustion; Extra-Role Customer Service; Job Performance; Lateness Attitude; Organizational Mission; Turnover Intentions

ÖZ : Bu tezin amacı, işletmede tanımlanmış olan misyonunun yerine getirilmesinin duygusal yorgunluk, işten ayrılma niyeti, işe geç kalma eğilimi, iş performansı ve ekstra role performansı üzerinde etkisini araştıran kavramsal bir modelin geliştirilmesi ve test edilmesidir. Bu ilişkilerin ölçülmesinde kullanılan veri Birleşik Arap Emirlikleri’nin turizm merkezi olan Dubai’deki uluslararası bş yıldızlı zincir otellerde faaliyet gösteren işgörenlerden toplanmıştır. Bu çalışanlar, müşterilerle yoğun bir şekilde birebir iletişimde olan kişilerdir. Değişkenler arası kullanılan zaman aralığı iki haftadır. İşgören performansına ilişkin veri, her bir işgörenin bağlı olduğu yöntecisinden toplanmıştır. Çalışmanın bulguları, duygusal yorgunluğun işletmede tanımlanmış olan misyonun işten ayrılma niyeti, işe geç kalma eğilimi, iş performansı ve ekstra role performansı üzerinde bir aracı rol oynadığını göstermiştir. Şöyle ki, misyonun başarılması işgörenlerin duygusal yorgunluğunu azaltmıştır. Bu durumda, işgörenlerin işten ayrılma niyeti ve işe geç kalma eğilimi azalmış, iş performası ve ekstra rol performansında artma meydana gelmiştir. Yukarıda verilen bulgular doğrultusunda yönetsel belirlemeler üzerinde durulmuş, araştırmanın sınırları ve gelecek araştırmalar için belirlemeler verilmiştir. Anahtar Kelimeler: Ekstra İş Performansı; Duygusal Yorgunluk; İşe Geç Kalma Niyeti; İşletme Misyonu; İşten Ayrılma Niyeti; İş Performansı
Master of Science in Tourism Management. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Tourism, 2015. Supervisor: Prof. Dr. Osman M. Karatepe.
Keywords: Tourism Faculty; Employee motivation; Work environment; Personnel management; Work - Psychological aspects; Employees - Job stress; Organizational behavior - Psychological aspects; Emotional Exhaustion; Extra-Role Customer Service; Job Performance; Lateness Attitude; Organizational Mission; Turnover Intentions